La parola scissa. Certeau e Barthes interpreti di Ignazio di Loyola - Facioni, Silvano (Bollettino Filosofico, 2019)
Michel de Certeau and Roland Barthes studied Ignazio di Loyola’s Spiritual Exercises by different perspectives, but the results of their investigations converge on a point: the writing of the Exercises constitutes a practice of interlocution in which otherness is investigated as extraneous in comparison to the order of the discourse. A real topic of the other is unfolded in the Exercises argumentative speech: the discourses create a space in which the other, who is at the same time desired and absent (or rather desired because absent and absent because desired), imposes himself as a menace and as a promise. Therefore, a comparison between Certeau and Barthes, allows to open a first path in which the other is, first of all, a performative writing, which invokes an interpretation beyond the ideologies. Keywords: Other, Text, Desire, Absence, Writing, Reading